Development of Gondosuli Coffee Network Expansion and Puspo Forest Honey Cultivation in Pasuruan Regency Throughout Indonesia to Improve Family Economy - Yuliati Yuliati; Puji Endah Purnamasari; Annisa Fatmawati Atu (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The largest contributor to local revenue in Pasuruan Regency is coffee, Puspo as a coffee plantation area also has a very valuable natural wealth and many benefits, namely forest honey. So far, coffee and honey productivity has only met the Pasuruan Regency area, through coaching, it is hoped that there will be an expansion of the marketing area and interest throughout Indonesia. This study aims to provide coaching to MSMEs in the Puspo area to improve the family economy by developing Gondosuli coffee and forest honey businesses. This research method is qualitative, with a case study as an approach, the interview technique used involves the main informant of the business owner and the supporting informant is a member of the Puspo MSME association, Pasuruan Regency. Data collection techniques using interviews, observations, and documentation. The results obtained from this study are Gondosuli Coffee which is identical to plantation products in the Puspo area has a distinctive taste of both Arabica, Robusta and Liberica, as well as forest honey from wasps. Puspo natural forest honey is a type of honey produced by wild bees that live in the Puspo Pasuruan forest area. The natural potential that is the advantage of the region is certainly not owned by other regions besides Puspo Pasuruan Regency. The obstacle faced by MSMEs in penetrating the national market is that all demand for packaged coffee and forest honey throughout Indonesia has not been met due to limited packaging technology so that production capacity is not large enough. There is no coffee storage warehouse that can help with the availability of coffee for all times. The contribution of research to help coffee and forest honey farmers in improving the family economy, with more durable packaging, is practically able to reach consumers throughout Indonesia.